The Merging of the Sacred and the Profane: What Substitutes for Ritual in the Baha'i Faith? - Momen, Moojan (Implicit religion, 2013)
The Baha'i Faith has very few communal rituals. There is little structure or set form to the regular meetings of the community or to such ceremonial occasions as weddings and funerals. Furthermore, there are textual instructions in the authoritative texts of the Baha'i Faith that prohibit the creation of a clerical class and the development of rituals over time. If then ritual is an essential part of religion, what substitutes for ritual in the Baha'i community? To answer this question, this paper goes back to Durkheims functionalist ideas that ritual creates the boundaries between the sacred and the profane (or secular), and also creates a sense of awe and an experience of the community as a living reality, reinforcing the sense of unity and strengthening the community. With regard to the first of these functions, in fact the boundaries between the sacred and the profane are deliberately blurred in the Baha'i Faith, and all of space and time potentially sacralized; conversely, it could be said that much of what would be regarded in other religious communities as sacred space and sacred time is secularized. With regard to the second of these functions, if Durkheims analysis is correct, ritual is not essential to religion for its own sake, but rather on account of the unity and reinforcement of the sense of community that it creates. When we come to consider the Baha'i Faith, there are a number of other factors that create unity and a sense of community. First, there are doctrinal factors such as the doctrine of the Covenant. Second, there are psychological factors such as a common vision (oneness of humanity and world unity). Third, there is the camaraderie of working together to achieve that vision-a common pathway along which all Baha'is are travelling. In all, these factors appear to be sufficient to substitute for the function of ritual in the Baha'i Faith.